Enhancing Students' Understanding of Social Sciences through Cooperative Learning Model at MIN 3 Ternate - Hamir Ahmad; Marniati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This research aims to explore the effectiveness of the Cooperative Learning model in enhancing students' understanding of Integrated Social Sciences (IPAS) at MIN 3 Ternate. The study was conducted with the goal of improving students' academic performance and engagement in the learning process. Cooperative Learning is a student-centered approach that emphasizes collaboration, where students work together in small groups to achieve shared learning goals. It is believed that this model can foster better understanding of complex subjects like IPAS by encouraging active participation, critical thinking, and peer support. The study was carried out in the 2024 academic year, involving students from the fourth and fifth grades at MIN 3 Ternate. Data was collected through pre-test and post-test assessments, as well as classroom observations and interviews with students and teachers. The results were analyzed to measure the improvements in students' comprehension of IPAS topics such as geography, history, and culture. Findings showed a significant improvement in students' academic achievements and engagement in the classroom after the implementation of the Cooperative Learning model. Students were more motivated, and their ability to grasp complex IPAS concepts improved due to the collaborative nature of the activities. The study also revealed that teachers' active facilitation and structured group activities played a crucial role in the success of this model. In conclusion, the implementation of Cooperative Learning in teaching IPAS at MIN 3 Ternate proved to be an effective strategy to enhance students' understanding and academic performance. The research suggests that this approach should be integrated into future instructional practices to foster deeper learning and greater student participation in social science education.